Pengenalan Awal Filsafat Pendidikan Islam (Pengertian, Ruang Lingkup, Dan Perkembangannya) - Khalid Hasan Minabari (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2019)
Al-Qur’an as the primary source of Islamic theology teaches a theology that led to the liberation of mankind from deterioration and repression. Therefore, some of the themes supporting his spirit of liberation theology, such as: freedom of thought and sense, psycho-social freedom, freedom to optimize the potential of unity, as the doctrine of social justice, freedom wanted-acting, struggle of liberation, as well as religious freedom and tolerance.